The Discriminatory Ability of Renalase and Biomarkers of Cardiac Remodeling for the Prediction of Ischemia in Chronic Heart Failure Patients With the Regard to the Ejection Fraction - Stojanovic, Dijana; Mitic, Valentina; Stojanovic, Miodrag; Petrovic, Dejan; Ignjatovic, Aleksandra; Milojkovic, Maja; Dunjic, Olivera; Milenkovic, Jelena; Bojanic, Vladmila; Deljanin Ilic, Marina (Frontiers in Cardiovascular Medicine, 2021)
Renalase has been implicated in chronic heart failure (CHF), however, nothing is known about renalase discriminatory ability and prognostic evaluation. The aim of the study was to assess whether plasma renalase may be validated as a predictor of ischemia in CHF patients stratified to the left ventricular ejection fraction (LVEF) and to determine its discriminatory ability coupled with biomarkers representing a range of HF pathophysiology: BNP, sST2, galectin-3, GDF-15, syndecan-1, and cystatin-C. Methods: A total of 77 CHF patients were stratified according to the LVEF and were subjected to exercise stress testing. Receiver-operating characteristic curves were constructed and the areas under curves (AUC) were determined, whereas the calibration was evaluated using the Hosmer-Lemeshow statistic. A DeLong test was performed to compare the AUCs of biomarkers. Results: Independent predictors for ischemia in the total HF cohort were increased plasma concentrations: BNP (p=0.008), renalase (p=0.012), sST2 (p=0.020), galectin-3 (p=0.018), GDF-15 (p=0.034) and syndecan-1 (p=0.024), whereas after adjustments, only BNP (p=0.010) demonstrated predictive power. In patients with LVEF<45% (HFrEF), independent predictors of ischemia were: BNP (p=0.001), renalase (p<0.001), sST2 (p=0.004), galectin-3 (p=0.003), GDF-15 (p=0.001) and syndecan-1 (p<0.001). The AUC of BNP (0.837) was statistically higher compared to those of: sST2 (DeLong test: p=0.042), syndecan-1 (DeLong: p=0.022), and cystatin C (DeLong: p=0.022). The AUCs of renalase (0.753), galectin-3 (0.726), and GDF-15 (0.735) were similar, and was non-inferior compared to BNP, regarding ischemia prediction. In HFrEF patients, the AUC of BNP (0.980) was statistically higher compared to those of: renalase (DeLong: p<0.001), sST2 (DeLong: p<0.004), galectin-3 (DeLong: p<0.001), GDF-15 (DeLong: p=0.001), syndecan-1 (DeLong: p=0.009), and cystatin C (DeLong: p=0.001). The AUC of renalase (0.814) was statistically higher compared to those of galectin-3 (DeLong: p=0.014) and GDF-15 (DeLong: p=0.046), and similar to that of sST2. No significant results were obtained in the patients with LVEF>45%. Conclusion:Plasma renalase concentration provided significant discrimination for the prediction of ischemia in patients with chronic heart failure, and appeared to have similar discriminatory potential to that of BNP. Although further confirmatory studies are warranted, renalase seems to be a relevant biomarker for ischemia prediction, implying its potential contribution to ischemia-risk stratification.